In Vitro and In Vivo Study of Gal‐OS Self‐Assembled Nanoparticles for Liver‐Targeting Delivery of Doxorubicin. Issue 3 (24th January 2014) - Guo, Hejian; Zhang, Dianrui; Li, Tingting; Li, Caiyun; Guo, Yuanyuan; Liu, Guangpu; Hao, Leilei; Shen, Jingyi; Qi, Lisi; Liu, Xinquan; Luan, Jingjing; Zhang, Qiang
<x xml:space="preserve">Abstract</x> A liver‐targeting drug delivery system for doxorubicin (DOX), that is, DOX‐loaded self‐assembled nanoparticles based on galactosylated O‐carboxymethyl chitosan‐graft‐stearic acid conjugates (Gal‐OS/DOX), has been prepared. The objective of the present study was to investigate the preparation, in vitro release, in vivo pharmacokinetics, and tissue distribution of Gal‐OS/DOX nanoparticles. The drug‐loaded nanoparticles were spherical in shape with mean size of 181.9 nm. In vitro release profiles indicated that the release of DOX from Gal‐OS/DOX nanoparticles behaved with a sustained and pH‐dependent drug release. Pharmacokinetics study revealed Gal‐OS/DOX nanoparticles exhibited a higher AUC value and a prolonged residence time of drug in the blood circulation than those of DOX solution. Furthermore, Gal‐OS/DOX nanoparticles increased the uptake of DOX in liver and spleen, but decreased uptake in heart, lung, and kidney in the tissue distribution study. These results suggested that the Gal‐OS/DOX nanoparticles could prolong blood circulation time, enhance the liver accumulation, and reduce the side effect especially the cardiotoxicity of DOX. In conclusion, Gal‐OS/DOX nanoparticles could be a promising drug delivery system for liver cancer therapy. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:987–993, 2014